The Euro's Challenge to the Dollar : Different Views from Economists and Evidence from COFER (Currency Composition of Foreign Exchange Reserves) and Other Data - Lim, Ewe-Ghee. (Washington, D.C. : International Monetary Fund, 2006)
This paper examines opposing views on the euro's challenge to the dollar as an international currency. One view emphasizes Europe's large economy and diversification effects as undergirding a vigorous challenge. The other emphasizes "network externalities," particularly undergirding continued dollar dominance. The data to date support the second view but also show the euro has significantly overtaken the legacy currencies as a reserve currency. Generally, large economic size alone is insufficient to challenge the network externalities supporting vehicle currencies, but scope exists for the euro to advance as an international store of value. The paper discusses the euro's medium-term prospects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet